The prevalence of Strongylida/strongyles in small ruminants in Manatuto Municipality in central region of Timor-Leste - Acacio Cardoso Amaral; Joana da Costa Freitas; Rui Daniel de Carvalho; Ana Maria da Costa Goncalves Noronha; Jaime Maria da Silva Ribeiro; Inocencio dos Santos (Livestock and Animal Research, 2022)
Objective: This research aimed to identify the prevalence of Strongyles in small ruminants (sheep and goats) in the central region of Timor-Leste.Methods: There were two methods used in this research, i.e. multistage sampling to determine research sites and purposive sampling to collect samples. The total samples collected were 192. From the 192 samples collected, 96 samples were from goats and another 96 samples from sheep. The sample size was determined based on 50% design prevalence and 95% confidence level and absolute precision of 10%. Samples examined were fresh fecal samples from sheep and goats. The samples were tested using a native smear to identify the presence of worms’ eggs in the feces. The 95% confidence interval of the prevalence was calculated using the exact binomial method.Results: Based on laboratory examination, it was found that the prevalence of Strongylida/strongyles in sheep was 21.88% (14.1-31.5%) and in goats was 20.83% (13.2-30.3%). Based on sex, the highest prevalence of Strongylida/strongyles of sheep was found in ram 25% (13.6-39.6%) compared to 18.75% (8.9-32.6%) in the ewe. In goats, however, the prevalence of Strongylida/strongyles was 25% (13.6-39.6%) in doe and 16.67% (7.5-30.2%) in bucks. Based on age, the highest prevalence in sheep was found in the age group of 9-12 months old 31.25% (16.1-50.0%), whereas in goats, the highest prevalence was found in the age group of 0-4 months old 28.13% (13.7-46.7%).Conclusions: Based on this research, it was identified that the prevalence of Strongylida/strongyles in small ruminants (sheep and goats) in the central region of Timor-Leste was 21.35% (15.8-27.8%).